Judgment day : [videorecording (DVD)] : intelligent design on trial (WGBH Boston Video, 2008)
"Judgment day: intelligent design on trial" captures the turmoil that tore apart the community of Dover, Pennsylvania, in a landmark battle over the teaching of evolution in public schools. In 2004, the Dover school board ordered science teachers to read a statement to high school biology students about an alternative to Darwin's theory of evolution called intelligent design--the idea that life is too complex to have evolved naturally and so must have been designed by an intelligent agent. The teachers refused to comply, and both parents and teachers filed a lawsuit in federal court accusing the school board of violating the constitutional separation of church and state. ... Featuring trial reenactments based on court transcripts and interviews with key participants and expert scientists, this program presents the case of Kitzmiller v. Dover School District."--Container.